Republic of Turkey - Williams, Joseph R. (Washington, D.C.)
1 mikrofiş (1. eser (4 poz ; s. 8-10), 2. eser (poz 5-13 ; s. 5-6, 133-140), 3. eser (poz 14-28 ; s. 5-6, 83-101), 4 eser (poz 29-31 ; 3 s.))